Ameliorative effects of rutin against metabolic, biochemical and hormonal disturbances in polycystic ovary syndrome in rats. Issue 1 (December 2016) - Jahan, Sarwat; Munir, Faryal; Razak, Suhail; Mehboob, Anam; Ain, Qurat; Ullah, Hizb; Afsar, Tayyaba; Shaheen, Ghazala; Almajwal, Ali
Abstract Background Polycystic ovary syndrome (PCOS) is the most prevalent endocrinopathy in women of reproductive age. The study was commenced to assess the favorable effects of Rutin against metabolic, biochemical, histological, and androgenic aspects of polycystic ovary syndrome in rats. Methods Female Sprague-Dawley rats were administered letrozole (1 mg/kg) per orally (p.o) for a period of 21 days for the induction of PCOS, followed by dose of rutin (100 mg/kg and 150 mg/kg, p.o) for 15 days using 0.5% w/v CMC as vehicle. Metformin was also given as a standard control to one of the rat groups. Serum estradiol, progesterone, testosterone, serum lipid parameters, CRP and glucose levels were evaluated. Furthermore, antioxidant activity was tested using superoxide dismutase, catalase, glutathione per-oxidase and reactive-oxygen species level. Results Rutin flavonoid had a dose-dependent effect on androgenic levels depicting more recovery in the rutin-I treated group, while rutin-II treated groups showed better antioxidant and lipid profiles as compared with PCOS groups. A decrease in the value of C reactive protein (CRP) and a restoration in the proportion of estrous phase smears were observed in the rutin treated groups. Histopathological examination of ovary revealed a significant decrease in the number of cystic follicles in post treated groups. The effects observed with rutin were moderately similar to that with standard metformin, a widely used treatment drug for PCOS. Conclusion The study provides evidence for the potential ameliorative effects of rutin against clinical and biochemical features of PCOS.